PENGARUH BENTUK BUKAAN TERHADAP KEKUATAN DAN GETARAN BALOK - Sunardi Klaten; Erny Listijorini; Raimundus Sandro (University of Muhammadiyah Jakarta, 2018)
Beam is widely used for building and mechanical structure. The beam characteristics must be able to answer the problem in field. In recent years, beam was made which compromised between stiffness and weight of beam. The beam has high stiffness but remains light. Beam was designed with opening (cellular) that can reduce its weight. The method used in this research was experimental and simulation with FEM. Geometric of cellular in this beam is a circle, square and rhombus by maintaining the same beam weight. The bending testing used is three-point bending method which is indicated stress and deflection. Output of vibration testing is frequency and damping constant. Damping constant is calculated by logarithmic decrement method. Research data show that dimension and geometric of beam cellular affect the strength and behavior of vibration significantly. Circular opening have the smallest stress and deflection in all conditions. The highest frequency and damping constant occur in rhombic opening 1.681 Hz and 84,88 kg/s respectively.